Effect of long-term intermittent hypothermia on random skin flap viability and new vessel formation - Ibrahim Baris Caglar (Turkish Journal of Plastic Surgery, 2020)
Background: Preconditioning is the improving the overall viability of the flaps before surgery. Hypothermia is one of preconditioning methods. In literature, the effect of short time hypothermia in skin flap viability has been studied. However, there is no information about the effects of long-term application of hypothermia on skin flap viability. In this study, we investigated the effect of long-term local hypothermia on flap viability and new vessel formation on random pattern skin flaps. Materials and Methods: Thirty-six adult male Sprague-Dawley rats were used. The flap model was, 3 cm × 9 cm sized random pattern skin flap. Three groups were composed as control group, continuous hypothermia induction group with ice bags, and intermittent hypothermia induction with chloroethyl spray. Flaps were raised on the 15th day of hypothermia sessions. Flap viability was measured in the software program. Microangiography and blood vascular endothelial growth factor (VEGF) levels were assessed for the detection of new vessel formation. Results: Average flap viabilities were found to be 64.87% in Group I, 57.69% in Group II, and 62.22% in Group III. The difference between Group II and other groups were statistically significant. When microangiographies were examined macroscopically, diameters, and amount of vascular branches of vessels in Group II were found to be higher than other groups. The difference between blood VEGF levels day 1 values among groups was not statistically significant. When day 4 values were compared to baseline values difference in Group III was statistically significant. At days 7 and 15, differences between groups and corresponding baseline values were not statistically significant. Conclusion: Continuous long-term application of hypothermia with ice-water bags causes a significant increase in neovascularization in random pattern skin flaps without an increase in skin flap viability. Hence, we can say that 2 weeks of hypothermia on random pattern skin flaps is not an efficient preconditioning method in clinical use.